Implementing the Mind Mapping Model to Improve Early Writing Skills Among Students of MIN 11 Pidie - Isra Wahyuni; Iswandi (Indonesian Journal of Education and Social Humanities, 2025)
This classroom action research was prompted by the low writing proficiency of Grade I-A students at MIN 11 Pidie, attributed to the prevalence of conventional lecture and assignment methods. This study aims to evaluate the effectiveness of the Mind Mapping model in improving student engagement and learning outcomes within the "Aku Istimewa" sub-theme. The methodology followed the Kemmis & McTaggart design, conducted in two cycles consisting of planning, action, observation, and reflection. Data were gathered through student behavior observation instruments, teacher performance rubrics, and learning achievement tests. The results demonstrated a significant increase in student active participation, reaching 100% by the end of Cycle II. Improvements in instructional quality were also observed across preparation (87.50%), presentation (85%), method application (80%), and teacher characteristics (91.67%). These findings confirm that idea visualization through Mind Mapping effectively bridges cognitive barriers in early writing, suggesting its viability as a pedagogical alternative in primary education.